2019
DOI: 10.1155/2019/3286928
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 Overexpression Attenuates Tubulointerstitial Fibrosis and Apoptosis in Diabetic Kidneys by Ameliorating Oxidative Injury via TXNIP-TRX

Abstract: Objective. The generation of hyperglycemia-induced reactive oxygen species (ROS) is a key event in diabetic nephropathy (DN) development. Since forkhead box class O1 (FOXO1) is associated with oxidative stress and shows a positive effect on DN, its role on renal function and the underlying mechanism is still unclear. Methods. We examined the role of FOXO1 in vivo (in a transgenic diabetic mouse model overexpressing Foxo1) and in vitro (in human HK-2 cells with FOXO1 knockin (KI) and knockout (KO) cultured unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 31 publications
0
52
0
Order By: Relevance
“…It can regulate FOXO1 through deacetylation, promote its expression and enhance its transcriptional activity . FOXO1 can reduce the damage of oxygen free radicals to kidneys by inducing autophagy . Our previous studies have shown that metformin could induce Sirt1‐FoxO1 autophagy signal axis, up‐regulate autophagy level, and inhibit cell proliferation, extracellular matrix and inflammatory factor secretion in glomerular mesangial cells induced by high glucose …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can regulate FOXO1 through deacetylation, promote its expression and enhance its transcriptional activity . FOXO1 can reduce the damage of oxygen free radicals to kidneys by inducing autophagy . Our previous studies have shown that metformin could induce Sirt1‐FoxO1 autophagy signal axis, up‐regulate autophagy level, and inhibit cell proliferation, extracellular matrix and inflammatory factor secretion in glomerular mesangial cells induced by high glucose …”
Section: Introductionmentioning
confidence: 99%
“…11 FOXO1 can reduce the damage of oxygen free radicals to kidneys by inducing autophagy. 12 Our previous studies have shown that metformin could induce Sirt1-FoxO1 autophagy signal axis, up-regulate autophagy level, and inhibit cell proliferation, extracellular matrix and inflammatory factor secretion in glomerular mesangial cells induced by high glucose. 13 In this study, we used a high-fat diet combined with streptozotocin (STZ) to establish diabetic rat model, and observed whether metformin exerted renal protective effect by regulating autophagy mediated by the Sirt11-FoxO1 signalling pathway in DN rats.…”
mentioning
confidence: 96%
“…In the present study, oral administration of Bak 1) reduced the mortality rate and improved the neurological function of animals after SAH, 2) attenuated disruption to the BBB and brain edema caused by SAH, 3) reduced the superoxide production, alleviated oxidative stress, and protected the mitochondrial ultrastructure during EBI, 4) attenuated SAH-induced cellular apoptosis and neuron damage, and 5) regulated the protein levels of Trx and TXNIP and the phosphorylation of AMPK. Moreover, both PX-12, a selective Trx inhibitor (Ji et al, 2019), and CC, a selective AMPK inhibitor (Oliveira et al, 2012;Guo et al, 2018), reversed the protective effects of Bak. To summarize, the present study confirmed that Bak can inhibit oxidative stress, attenuate cellular apoptosis, and ameliorate BBB disruption via regulating the protein level of Trx and the activity of AMPK after SAH ( Figure 6).…”
Section: Discussionmentioning
confidence: 95%
“…and oxidative stress (Ji et al, 2019). Trx2, the main ROSscavenging enzyme in mitochondria, balances ROS levels and maintains mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Forkhead box transcription factors are required for normal tissue specification, differentiation, maintenance, and function [34][35][36]. Foxp1, a newly discovered member of the forkhead box family, plays key roles in progression of several diseases including diabetes and in processes such as fibrosis and apoptosis [37]. In our study, we found that HS loading significantly reduced the expression of Foxp1 in the renal tissues of Dahl-S rats at both mRNA and protein level, while treatment with reCREG restored Foxp1 expression in renal tissues.…”
Section: Discussionmentioning
confidence: 99%